PENINGKATAN KESEJAHTERAAN DAN KEMANDIRIAN MASYARAKAT DESA DENGAN INOVASI PANGAN PANGSIT MUJAIR - Saraswati, S.A.; Pebriani, D.A.A.; Negara, I.K.W.; Pratiwi, M.A.; Wijayanti, N.P.P. (Buletin Udayana Mengabdi; Vol 20 No 3 (2021): Buletin Udayana MengabdiDO - 10.24843/BUM.2021.v20.i03.p12, 2022)
Dumplings made from tilapia are made from natural herbs and spices without additional flavoring and coloring, so that these foods do not threaten the health of those who consume them. This dumpling has a characteristic tilapia and vegetable mixture that makes this food high in nutritional value, low in cholesterol, rich in fiber, and contains lots of omega that is good for health. Gesing Village, Buleleng Regency, Bali has tilapia fishponds. Mujair dumpling making training is deemed necessary to be carried out in Gesing Village to process abundant tilapia production. The training will be held in Gesing Village, Buleleng Regency, namely the Independent Cultivators Group. Through training in making tilapia dumplings, it is hoped that the people in Gesing Village can take advantage of their crops so that they can improve their prosperity and independence in entrepreneurship. Keywords : Dumplings, Gesing Village, Food Innovation, Processed Products, Mujair